Decomposing the percolation backbone reveals novel scaling laws of the current distribution - Sena, Wagner R. de; Andrade, José S.; Herrmann, Hans J.; Moreira, André A. (Frontiers in Physics, 2023)
The distribution of currents on critical percolation clusters is the fundamental quantity describing the transport properties of weakly connected systems. Nevertheless, its finite-size extrapolation is still one of the outstanding open questions concerning disordered media. By hierarchically decomposing the 3-connected components of the backbone, we disclose that the current distribution is determined from two distributions, namely, the one corresponding to the number of bonds in each level and another one corresponding to the factors by which the current is reduced, when going from one level to the next. The first distribution follows a finite-size scaling, while the second is a power law with an exponent consistent with 3/4 in two dimensions. The standard hierarchical model for the backbone is too simple to reproduce this complex scenario. Our new decomposition method of the backbone also allows to calculate much smaller currents than before, attaining precision of 10 −35 and systems of size L = 8192 2 . Moreover, our method is not restricted to electric currents on critical percolation clusters but could also be applied to other trnsport problems on sparse graphs including fluid flow and car traffic.